Meals in Minutes - Harriott's, Ainsley (London BBC Books, 2005)
Ainsley shows us how to serve up speedy meals without compromising on quality or taste great food, fast, for busy people. So even though we work hard, play hard and definitely have less time for cooking, if we follow Ainsley's example we can create scrumptious meals on the spur of the moment and make take-aways a thing of the past
Include Colors Illustration,Index
Keywords: Quick and easy cooking -- Cooking